RATIONALE FOR CHOOSING THE CHANGE MODEL OF THE DIELECTRIC PROPERTIES OF DISCONTINUOUS SYSTEMS - Trykoz, L. V.; Bahiiants, I. V. (Science and Transport Progress, 2016)
Purpose. The article deals with the insulation resistance of the track circuit as one of the parameters that affect the operating performance of the railway transport. To reduce the influence of the insulation resistance on the operation modes of the track circuits and the performance indicators of railway transport it is assumed to study the influence of crushed stone treatment on the value of dielectric permeability of the ballast bed. Methodology. The influence of material type for the surface treatment of crushed stone on the value of the dielectric permeability was assessed on the basis of the physical nature determination of the relative dielectric permeability. Determination of the relative dielectric permeability of granular media can only be indirect, as a consequence of incomplete adjoining of crushed stone grains and uncertainty of the pore volume. Thus, the calculations were performed by comparing the measured capacity for a medium with the known with measured medium capacity, for which it is necessary to define. That is, the more the measured capacity is changed, the more changes the dielectric permeability of the medium. Findings. Sleepers and ballast significantly change their electrical conductivity depending on the presence of moisture, ambient temperature changes, the presence of pollutants and other factors. The article analyzes the existing models to describe the dielectric properties of such systems. It has been established that coating the crushed stone ballast with organic substances influences the value of its relative dielectric permeability. The greatest effect of reducing this value is observed for the coatings based on rosin mixture and silicone. Originality. Authors proposed original method of dielectric properties increase of the permanent way by grains’ coating with nonwettable substances, on the surface of which is not formed a water film. Practical value. The article shows the possibility of minimizing the negative influence of reducing the isolation with maximum its elimination. It is proposed the solution of actual problem by eliminating the influence of insulation resistance on the modes of track circuits operation, which will eliminate the part of causes of the failure of signaling devices and reduce the number of cases of «false business».